Looking for luxury CSR practices that make more sense: The role of corporate identity and consumer attitude. Issue 6 (17th August 2020) - Panigyrakis, George; Panopoulos, Anastasios; Koronaki, Eirini
ABSTRACT: This paper explores the factors affecting consumers' evaluation of luxury corporate social responsibility (CSR) practices. In particular, it examines how corporate identity and consumer attitude influence the importance they attribute to a variety of luxury CSR practices. The existing academic literature neglects this question, and there has been a call for understanding which type of CSR practices is appropriate for luxury brands. Findings from an empirical study regarding the French luxury brand Hermes indicate that corporate identity is a significant predictor of which CSR practices consumers evaluate as important. As well that, consumer attitude mediates the latter effect. The current research thereby stresses the need for luxury brand managers to link CSR practices to corporate identity and to acknowledge how consumers' attitude can affect this relationship.